ANALISIS “FINANCIAL TEKNOLOGY (FINTECH)” PADA PERMODALAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DENGAN MODEL PEER-TO-PEER (P2P) LENDING - Ria Manurung (Jurnal Keuangan dan Bisnis, 2019)
The purpose of this study is to analyze the impact of Fintech on Micro Small and Medium Enterprises (MSME) capital with the P2P Lending model. Research locations in the Banyumas Regency area with a concentration of 110 MSME as a research sample, with the criterion that ever or currently lending with P2P Lending system. Primary data were obtained from the results of questionnaire processing and interviews with respondents, namely MSME, while secondary data was sought from OJK, BPS, the Ministry of Cooperatives and Micro, Small and Medium Enterprises, BI, articles, and textbooks relevant to research. Data analysis methods are descriptive analysis methods, paired difference analysis and ordinary least square (OLS). The conclusion obtained in this study is a tendency to increase in the Number of Workers, Turnover, Product Sales, Profits and Business Costs after the use of Fintech with the Peer to Peer (P2P) Lending model in MSME. So venture capital loans obtained through FinTech with the P2P Lending model have a positive effect on the improvement and development of the MSME business.